2021
DOI: 10.3390/ijms222111896
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ZNT1 and NRAMP4 from the Ni Hyperaccumulator Noccaea caerulescens Population Monte Prinzera in Arabidopsis thaliana Perturbs Fe, Mn, and Ni Accumulation

Abstract: Metalliferous soils are characterized by a high content of metal compounds that can hamper plant growth. The pseudometallophyte Noccaea caerulescens is able to grow on metalliferous substrates by implementing both tolerance and accumulation of usually toxic metal ions. Expression of particular transmembrane transporter proteins (e.g., members of the ZIP and NRAMP families) leads to metal tolerance and accumulation, and its comparison between hyperaccumulator N. caerulescens with non-accumulator relatives Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Although the Ni contents were dramatically increased in the Ni treated plants of both genotypes, yuc6-1D contained significantly more (10.5% more) Ni than Col-gl ( Figure 3A ). Ni treatments reduce manganese (Mn) and iron (Fe) availability for plants, both of which are necessary for chlorophyll biosynthesis and photosynthesis ( Rahman et al., 2005 ; Fasani et al., 2021 ; Rai et al., 2021 ). Our data showed that Ni stress decreased the Mn and Fe contents to a similar extent in Col-gl and yuc6-1D ( Figures 3B, C ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the Ni contents were dramatically increased in the Ni treated plants of both genotypes, yuc6-1D contained significantly more (10.5% more) Ni than Col-gl ( Figure 3A ). Ni treatments reduce manganese (Mn) and iron (Fe) availability for plants, both of which are necessary for chlorophyll biosynthesis and photosynthesis ( Rahman et al., 2005 ; Fasani et al., 2021 ; Rai et al., 2021 ). Our data showed that Ni stress decreased the Mn and Fe contents to a similar extent in Col-gl and yuc6-1D ( Figures 3B, C ).…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic expression of ZNT1 cloned from Noccaea caerulescens (J.Presl & C.Presl) F.K.Mey. revealed that NcZNT1 contributed greatly to root-shoot transport of metals such as nickel, Cd, zinc, iron (Fe), and manganese (Mn) in A. thaliana [38]. The upwards transport of Fe and Mn rather than Cu or Zn was increased in transgenic A. thaliana overexpressing SnYSL3 (Solanum nigrum L.), but when stressed by Cd the transport efficiency of Mn no longer changed [39].…”
Section: Discussionmentioning
confidence: 99%